Conceptual Review and the Production, Consumption and Price Models of the Natural Rubber Industry in Selected ASEAN Countries and World Market - Fong, Yi Chiun; Khin, Aye Aye; Lim, Chee Seong (Asian Journal of Economic Modelling, 2018)
Natural rubber (NR) is one of the crucial commodities in the world and also extensively used in many applications and products. The objectives of the study are to develop the conceptual review and to analyze the production, consumption and price models of the NR in selected ASEAN countries and world market. The production model is the function of the NR price for five selected ASEAN countries such as Thailand, Indonesia, Malaysia, Vietnam and Myanmar. The consumption model is the function of the domestic NR price and domestic stock of the four largest rubber consuming countries which are China, India Japan and USA. The world NR price model (Singapore SICOM price) involves the factors such as NR production, NR consumption, real exchange rate, and crude oil price. Panel data analysis was performed for the NR production and consumption models by using annual data from year 1997 to 2017; and Vector Error Correction Method (VECM), cointegration test and Granger Causality test were analyzed on the world NR price model using monthly data from January 2008 to December 2017. Lastly, a contribution of this study would be the interest of policymakers for policy implication of the businesses and manufacturing industries that are closely related to rubber.